Standard tests ability to measure impact forces reduction on mats - Perez, P.; Llana, S.; Alcantara, E. (International Journal of Sports Science and Engineering, 2008)
Landing is one of the most important and dangerous actions that a gymnast takes. Although landing mats are supposed to meet standard criteria, the number of injuries in this action continues being high, which has raised questions as to the validity of the standard. In this study was analysed the effect of the mat on different kinematical and kinetic variables during gymnast landing, and it was examined the validity of normative tests to predict such variables. 5 elite gymnasts performed several landings on a sample of 6 mats previously selected on the basis of their mechanical behaviour. Maximum vertical reaction forces and peak tibial and forehead acceleration were analysed, with average maximum reaction force of 4450 ± 195.34 N, and 15.57± 0.54 g and 4.72 ± 0.55 g on tibial and forehead acceleration respectively. Gymnasts modulate execution based on mat properties, and not all the biomechanical variables studied are faithfully reproduced in the mechanical tests of the standard, which could have some influence on the occurrence of certain injuries.